Effect of airtime incentives on response and cooperation rates in non-communicable disease interactive voice response surveys: randomised controlled trials in Bangladesh and Uganda. Issue 5 (6th September 2019) - Gibson, Dustin G; Wosu, Adaeze C.; Pariyo, George William; Ahmed, Saifuddin; Ali, Joseph; Labrique, Alain B; Khan, Iqbal Ansary; Rutebemberwa, Elizeus; Flora, Meerjady Sabrina; Hyder, Adnan A
Abstract : Background: The global proliferation of mobile phones offers opportunity for improved non-communicable disease (NCD) data collection by interviewing participants using interactive voice response (IVR) surveys. We assessed whether airtime incentives can improve cooperation and response rates for an NCD IVR survey in Bangladesh and Uganda. Methods: Participants were randomised to three arms: a) no incentive, b) 1X incentive or c) 2X incentive, where X was set to airtime of 50 Bangladesh Taka (US0.60) and 5000 Ugandan Shillings (UGX; US1.35). Adults aged 18 years and older who had a working mobile phone were sampled using random digit dialling. The primary outcomes, cooperation and response rates as defined by the American Association of Public Opinion Research, were analysed using log-binomial regression model. Results: Between 14 June and 14 July 2017, 440 262 phone calls were made in Bangladesh. The cooperation and response rates were, respectively, 28.8% (353/1227) and 19.2% (580/3016) in control, 39.2% (370/945) and 23.9% (507/2120) in 50 Taka and 40.0% (362/906) and 24.8% (532/2148) in 100 Taka incentive groups. Cooperation and response rates, respectively, were significantly higher in both the 50 Taka (risk ratio (RR) 1.36, 95% CI 1.21 to 1.53) and (RR 1.24, 95% CI 1.12 to 1.38), and 100 Taka groups (RR 1.39, 95% CI 1.23 to 1.56) and (RR 1.29, 95% CI 1.16 to 1.43), as compared with the controls. In Uganda, 174 157 phone calls were made from 26 March to 22 April 2017. The cooperation and response rates were, respectively, 44.7% (377/844) and 35.2% (552/1570) in control, 57.6% (404/701) and 39.3% (508/1293) in 5000 UGX and 58.8% (421/716) and 40.3% (535/1328) in 10 000 UGX groups. Cooperation and response rates were significantly higher, respectively in the 5000 UGX (RR 1.29, 95% CI 1.17 to 1.42) and (RR 1.12, 95% CI 1.02 to 1.23), and 10 000 UGX groups (RR 1.32, 95% CI 1.19 to 1.45) and (RR 1.15, 95% CI 1.04 to 1.26), as compared with the control group. Conclusion: In two diverse settings, the provision of an airtime incentive significantly improved both the cooperation and response rates of an IVR survey, with no significant difference between the two incentive amounts. Trial registration number: NCT03768323 .